A dual simplex method for grey linear programming problems based on duality results. Issue 2 (30th April 2020) - Darvishi Salookolaei, Davood; Nasseri, Seyed Hadi
Abstract : Purpose: For extending the common definitions and concepts of grey system theory to the optimization subject, a dual problem is proposed for the primal grey linear programming problem. Design/methodology/approach: The authors discuss the solution concepts of primal and dual of grey linear programming problems without converting them to classical linear programming problems. A numerical example is provided to illustrate the theory developed. Findings: By using arithmetic operations between interval grey numbers, the authors prove the complementary slackness theorem for grey linear programming problem and the associated dual problem. Originality/value: Complementary slackness theorem for grey linear programming is first presented and proven. After that, a dual simplex method in grey environment is introduced and then some useful concepts are presented.